Synchronized bilateral percutaneous nephrolithotripsy in a horseshoe kidney - R Krishna Rao; M S Ranganath; T Krishna Prasad (Indian Journal of Urology, 2008)
Stone management in horseshoe kidneys is challenging: percutaneous nephrolithotripsy is a safe and effective procedure in the treatment of large stones within horseshoe kidneys. Simultaneous bilateral PCNL has been described with a single surgeon operating sequentially on one renal unit following the other under the same anesthetic. We describe synchronized bilateral PCNL by two operating teams in tandem for a patient with bilateral stag horn calculi associated with a horseshoe kidney.